A simpler and faster algorithm to compute Induced Star Partitions in graphs - Gomes, Guilherme C. M.; Prates, Matheus T. (Anais do Encontro de Teoria da Computação (ETC); 2025: Anais do X Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2025.7517, 2025)
An induced star partition of a graph is a partition of its vertex set in which all parts must induce a star, i.e., each part i must induce a subgraph isomorphic to a K 1,ti for some t i ≥ 1. We present a new algorithm for computing one such partition, which improves on previous results in the literature, being both simpler and more efficient.